Sistem Prediksi Sisa Waktu Nyala Baterai Uninterruptible Power Supply Lampu Kandang Ayam menggunakan Regresi Linier - Muhammad Taufiq Azra Haromain; Eko Setiawan; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
One of the problems when chickens breeding is that many chickens become stress or even die due to the condition of the chicken coop, which suddenly becomes dark due to a sudden power outage. Of course, this will be detrimental to chicken farmers. One solution to keep the lights from going out suddenly is to use a UPS. UPS usage is temporary and the light will remain off when the battery runs out. Therefore, the author wants to create a system that can back up power using an Uninterruptible Power Supply (UPS) and can predict the remaining UPS on time using the linear regression method based on the results of the UPS battery voltage readings made by the voltage sensor. This system is connected to the lamp power and system output, namely the UPS battery voltage. The prediction of the remaining UPS time can be accessed at the website address which will be sent to the user's telegram when the system detects a power outage. Based on testing, the voltage sensor has an average offset value of 0.27V with an error rate of 2.1%. The linear regression equation obtained from the initial dataset is Y = -81.33 + 7.85X. The results of testing the prediction accuracy of the remaining UPS on using the linear regression method on this system obtained an MAPE value of 6.64%.